The Type II Topp-Leone Generalized Power Ishita Distribution with Properties and Applications - Friday Ikechukwu, Agu; Thomas Eghwerido, Joseph; Francis Emmanuel, Runyi (Thailand Statistician, 2021)
Motivated to obtain a flexible distribution. In this paper, we proposed a compound continuous distribution called the type II Topp-Leone power Ishita generalized (TIITLPI-G) distribution. Some of the basic statistical properties of the TIITLPI-G distribution are examined and the parameters are obtained using method of maximum likelihood estimation. The flexibility and the superiority of the proposed TIITLPI-G distribution were demonstrated by means of numerical applications on two sets of real life data. The proposed TIITLPI-G distribution was compared with other existing distributions in literature in terms of fitness and the result obtained indicates that the proposed TIITLPI-G distribution outperformed the competing distributions in terms of fitness.